2013
DOI: 10.1371/journal.pone.0056148
|View full text |Cite
|
Sign up to set email alerts
|

The Periglomerular Cell of the Olfactory Bulb and its Role in Controlling Mitral Cell Spiking: A Computational Model

Abstract: Interneurons in the olfactory bulb are key elements of odor processing but their roles have not yet being fully understood. Two types of inhibitory interneurons, periglomerular and granule cells, act at two different levels within the olfactory bulb and may have different roles in coordinating the spiking of mitral cells, which are the principal output neurons of the olfactory bulb. In this work we introduce a reduced compartmental model of the periglomerular cell and use it to investigate its role on mitral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
2
20
0
2
Order By: Relevance
“…MCs were located below the GCs, in a single lamina, the MC layer, with their dendrites spanning the OB, and showed more depolarized resting potentials compared with GCs (−53.2±1.12 mV, N=13 versus −66.5± 1.55 mV, N=4; mixed model, F 1,15 =35.86, P<0.0001; Fig. 2B,C) in agreement with previous studies (Chen and Shepherd, 1997;Heyward et al, 2001;Scheidweiler et al, 2001;Arruda et al, 2013). In MCs, action potentials evoked by threshold current injections occurred with a long delay of up to 300 ms (N=13, Fig.…”
Section: Statistical Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…MCs were located below the GCs, in a single lamina, the MC layer, with their dendrites spanning the OB, and showed more depolarized resting potentials compared with GCs (−53.2±1.12 mV, N=13 versus −66.5± 1.55 mV, N=4; mixed model, F 1,15 =35.86, P<0.0001; Fig. 2B,C) in agreement with previous studies (Chen and Shepherd, 1997;Heyward et al, 2001;Scheidweiler et al, 2001;Arruda et al, 2013). In MCs, action potentials evoked by threshold current injections occurred with a long delay of up to 300 ms (N=13, Fig.…”
Section: Statistical Analysessupporting
confidence: 92%
“…In MCs, action potentials evoked by threshold current injections occurred with a long delay of up to 300 ms (N=13, Fig. 2B showed that MCs of control tadpoles had an input resistance of 184.7±17.7 MΩ (N=13), which is significantly lower than that of GCs (315.5±7.9 MΩ, N=4; mixed model, F 1,14 =9.13, P=0.009), according to previous studies (Chen and Shepherd, 1997;Scheidweiler et al, 2001;Arruda et al, 2013;Heinbockel et al, 2004). The resting potential of MCs did not differ between control and treated tadpoles (respectively, −53.2±1.12 mV, N=13 and −54.2± 0.03 mV, N=13; mixed model, F 1,24 =0.43, P=0.52; Fig.…”
Section: Statistical Analysessupporting
confidence: 79%
“…The network model was constrained by experimental data: in addition to incorporating biophysically realistic circuit elements, sensory input to the model OB network was derived from recordings of ORN inputs to the OB of intact rats, and an experimental dataset of presumptive MC recordings, evoked by the same naturalistic sniffing patterns used to drive the ORN responses, was used as a benchmark for evaluating model output. The use of input waveforms with naturalistic dynamics differs from the constant, pulsatile or sinusoidal inputs used in most earlier network models of olfactory processing (Arruda et al 2013;Bathellier et al 2006;Brody and Hopfield 2003;Davison et al 2003 ET-MC , maximum conductance for ET-MC synapse; g ET-PG ET , maximum conductance for ET-PG ET synapse; g PG ET -MC , maximum conductance for PG ET -MC synapse. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the model does not analyze the role periglomerular cells play in the olfactory information encoding process. These issues are further studied and discussed in the author's doctoral dissertation [36].…”
Section: Heterogeneity Of Periglomerular Cellsmentioning
confidence: 99%
“…At present, research teams at the University of Sao Paulo, Brazil, and Zhejiang University are studying the functional mechanism of periglomerular cells under a complete olfactory bulb cell network model [36,37]. This study combines mitral cells and granule cells to build a three-layer olfactory network model that is then used to analyze the function of PG cells in olfactory bulb encoding.…”
Section: Investigating the Cellular Mechanisms Of Periglomerular Cellmentioning
confidence: 99%